2017
DOI: 10.1088/1367-2630/aa8b01
|View full text |Cite
|
Sign up to set email alerts
|

Quantum metrology in local dissipative environments

Abstract: Quantum metrology allows us to attain a measurement precision that surpasses the classically achievable limit by using quantum characters. The metrology precision is raised from the standard quantum limit (SQL) to the Heisenberg limit (HL) by using entanglement. However, it has been reported that the HL returns to the SQL in the presence of local dephasing environments under the long encoding-time condition. We evaluate here the exact impacts of local dissipative environments on quantum metrology, based on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 67 publications
(130 reference statements)
1
25
0
Order By: Relevance
“…Many of these studies are typically concerned with estimating the frequency ω rather than the phase f; the two parameters are related to each other by the encoding time t, i.e., f=ω t. Thus, the total running time of the encoding process itself is regarded as a resource [13]. These studies have shown that a super-extensive growth of the frequency sensitivity may still be attained under time-inhomogeneous, phase-covariant noise [26][27][28][29][30], and even more generic Ohmic dissipation [31], noise with a particular geometry [32,33], or setups related to quantum error correction [34][35][36]. See also [37,38] which question the role of entanglement in such schemes and give advice on practical implementations.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies are typically concerned with estimating the frequency ω rather than the phase f; the two parameters are related to each other by the encoding time t, i.e., f=ω t. Thus, the total running time of the encoding process itself is regarded as a resource [13]. These studies have shown that a super-extensive growth of the frequency sensitivity may still be attained under time-inhomogeneous, phase-covariant noise [26][27][28][29][30], and even more generic Ohmic dissipation [31], noise with a particular geometry [32,33], or setups related to quantum error correction [34][35][36]. See also [37,38] which question the role of entanglement in such schemes and give advice on practical implementations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that such a bound state has profound impacts on many quantum protocols and nonequilibrium physics, e.g. entanglement preservation [28][29][30], noncanonical thermalization [31], quantum speed limit [32], and quantum metrology [33][34][35]. The results give us an insightful guideline to control decoherence via forming the bound state by quantum reservoir engineering [36,37].…”
Section: Introductionmentioning
confidence: 98%
“…To deal with this issue, dynamical decoupling 5,25 , feedback control [26][27][28] and many other approaches have been developed. Moreover, non-Markovian effect is also shown to be effective to maintain entanglement-induced high measurement precision 29,30 . Most of the above works focus on how to prepare or protect entangled states for quantum metrology.…”
Section: Introductionmentioning
confidence: 99%